You make me shine the making of a gay icon by the gay fandom of Regine Velasquez - Galang, Eric John Joaquin R. 1999; Sanchez, Louie Jon A. (Quezon City College of Mass Communication, University of the Philippines, 2023)
The recent increasing penetration and inclusion of gay audiences as agents in Philippine mass media subsequently welcome the viewing of Filipino celebrities through a queer lens, especially those who characteristically have amassed a gay following. Regine Velasquez is one of them, which all the more makes her a gay icon. As the study recognizes the queer developments in Philippine mass media and popular culture, it acknowledges their effects on audience reception. identity-building among audiences, fandom, stardom, and their respective academic disciplines. Furthermore, this study views the significance of the active participation of fans in the making of an icon. It is because of the intricate complexity of gay iconicity and identity that the research opted to examine the process by which a celebrity becomes a gay icon in the particular case of Regine Velasquez who, since the 90s and to this day, has made significant strides in the entertainment industry. In line with a qualitative research design, the study probed 10 gay fans of Regine Velasquez. The experiences of these fans are this study's units of analysis. Guided by theoretical developments to Laura Mulvey's male gaze, Jonathan Cohen's identification, and empirical studies about diva worship, with an overarching queer lens, this study will locate Regine Velasquez fans and how their identification, veneration, and productivities contribute to the gay iconicity of the Asia's Songbird.
Dahil sa kamakailang paglaganap at pagpasok rig mga baklang manunuod bilang aktibong pwersa sa Philippine mass media, laganap na rin ang pagtingin sa mga Pilipinong artista gamit ang 'queer lens' lalo't higit sa mga artistang mayroong, maraming baklang taga-hanga. Isa si Regine Velasquez sa mga ito, kung kaya't siya ay mas nagiging isang 'gay icon.' Habang kinikilala ng pag-aaral na ito ang mga pag-unlad ng usaping 'queer' sa Philippine mass media at kulturang popular, isinasaalang-alang din nito ang bungang dulot sa pagtanggap ng mga manunuod, paggawa ng identidad bilang manunuod, fandom, stardom, at ang kani-kanilang kaakibat na pang-akademikong disiplina. Dahil dito, tinitignan ng pag-aaral na ito ang kahalagahan ng aktibong partisipasyon ng mga taga-hanga sa paghuo ng isang icon. Ang pagsusuri sa proseso ng pagiging isang gay icon ng isang artista sa partikular na sitwasyon ni Regine Velasquez, na simula pa noong 90s hanggang sa kasalukuyan ay nakagawa ng mahahalagang kontribusyon sa industriya ng entertainment, ay buhat ng komplikasyong nakapaloob sa gay iconicity at identidad. Sa pamamagitan ng isang qualitative research design, ang pag-aaral na ito ay gagamit ng panayam ng mga baklang raga-hanga ni Regine Velasquez. Ang unit of analysis ng pag-aaral na ito ay ang kolektibong danas at pagtingin ng 10 na taga-hangang ito. Sa tulong ng mga teoretikal na pag-unlad sa male gaze ni Laura Mulvey. identification ni Jonathan Cohen, mga impirikal na pag-aaral ukol sa diva worship,. gamit ang isang pangkabuuang queer lens, ang pag-aaral na ito ay tutukuyin ang mga taga-hanga ni Regine Velasquez at kung papaano nakatutulong ang kanilang identification, veneration, at productivities sa pagiging isang gay icon ng Asia's Songbird.
Vita.
Thesis
Includes bibliographical references (pages 198-213) and appendices (pages 214-280).
Keywords: Fans (Persons) in mass media; Gay people in mass media